Sustainable practices for reduction of environmental footprint in tanneries of Pakistan - Mehak Sikander (Elsevier, 2021)
The research focuses on implementation of cleaner production techniques and sustainable practices to reduce the environmental footprint in 07 tanneries of Pakistan through the project titled, International Labour and Environmental Standards (ILES) in SEMs of Pakistan by WWF-Pakistan. The baseline data of the industries were collected, and each industrial unit was surveyed for 05 days to cover all the major areas of resource and energy consumption, chemical conservation, reduction in CO2 emission and economic feasibility including payback period and profit. Collected data were analyzed and suitable technological solutions were proposed for the opportunities. After a specific time, post-performance analysis was carried out to ensure the on-ground implementation and to develop strong business cases. Gaps were shared with the examined industries for their internal use and continuous improvements for further reduction in their environmental footprint. It was concluded that by working on the suggested interventions 07 industries, on average, conserved 71,131 m3 water per year, 1643.166 m3 per year compressed air was saved, and 333,791 kW energy was conserved on a yearly basis. Steam management helped industries to save 136,398 kg of steam on a daily basis, and the overall CO2 reduction was 300,842 kg/year. The graphical abstract below indicates the resources conserved by the industries that ultimately save the cost and reduce CO2 emission.Resource Conservation and GHG Reduction by 07 Tanneries.